MATHEMATICS LEARNING IN THE SOUTHEAST ASIA REGION ON THE SCOPUS DATABASE: BIBLIOMETRIC ANALYSIS (1993-2024) - Gunawan, Resky Nuralisa; Mutiara, Era; Zafrullah, Zafrullah; Majid, Mohamed Hasan Mohamed; Nur, Muhammad Imran; Mwakapemba, James Leonard (UIR PRESS, 2024)
This research aims to analyze research trends regarding mathematics learning in Southeast Asia on the Scopus Database. Using existing keywords, researchers selected using the PRISMA method and obtained 829 documents which were analyzed using VOSviewer and the R Program. From the results of the analysis, it can be concluded that research on mathematics learning in Southeast Asia began in 1993 and showed significant development until 2024, with a total of 829 documents published from 200 sources. Despite a decline in publications in 2013, the overall publication trend continues to show positive growth, especially after 2012. Indonesia occupies the top position in the number of publications and citations, followed by Malaysia, with Nanyang Technological University in Singapore being the leading institution. The various research focuses reflect efforts to improve the quality of mathematics learning in the region. Apart from that, the latest topics such as “online learning”, “ethnomathematics”, and “flipped classroom” are very relevant to be applied in facing educational challenges in the current digital era.